COVID-19 VACCINE UPTAKE AMONG OPULENT VS SLUMS OF URBAN SETTING IN KARACHI, PAKISTAN - Seemi, Tooba; Sharif, Hina; Sheikh, Sana Sharif; Hashmi, Muzna; Naeem, Hira (Universitas Airlangga, 2024)
Background: COVID-19 vaccine effectiveness and acceptability are critical for a number of important outcomes, including symptomatic COVID-19, severe illnesses, and COVID-19-related mortality. Aim: To assess the immunization status regarding age, gender, and living standards and the reason for non-compliance to the Covid-19 vaccine among people of urban opulent and slums areas of a single city, i.e., Karachi, Pakistan. Method: This cross-sectional study was conducted from December 2022 to January 2023 in Karachi, Pakistan. Data were collected through social media websites, including WhatsApp and Facebook, telephonic interviews from opulent urban areas, and direct contact during the visit to primary health care clinics in urban slum areas. STATA software was used for data analysis. Result: Of 1265 respondents from slums and opulent areas, 15.8% were non-vaccinated slums, whereas 14.16% belonged to opulent areas needing vaccination with adjusted OR 95% is 0.74(0.41-0.95). Of 1265 respondents, 825(65%) were females, and 440 (34.7%) were male. The vaccine compliance among females was 49%, and 32% among male respondents with adjusted OR 95% 1.84(1.12-3.03). Only 6% of the slums area were vaccinated with the required shots of vaccine (2 doses and one booster) compared to opulent areas, i.e., 20%. Conclusion: Our research at the population level adds to the knowledge we now have from patient data and demonstrates how aggregated data from fully functioning epidemic surveillance and monitoring may provide information about the possible effects of extended COVID on national and international public health.